A case study: A technological insight on teaching translation. (14th July 2022) - Pardo‐Ballester, Cristina
Abstract: This case study examines an online introductory Spanish‐English translation course focused on learning Spanish through machine translation. Fifty‐three Spanish learners were guided by their teacher to rethink, reflect, and interpret what Google Translate offered. Quantitative and qualitative analyses of learners' reports and teacher feedback revealed that the evaluative task design led to (a) high percentages of learners' interlinguistic and intercultural awareness and (b) translation methods awareness for more than half of the learners. Participants' responses to a literary translation assignment were explored through teacher scaffolding for learners to understand how to differentiate lexical to phrasal levels in a text, with the aim to translate also the style of the source text for the American audience. Pedagogical implications will be shared on how a teacher‐learner approach on translation tasks prepared students for the language awareness learning process. The Challenge: Google Translate has become the language learners' strategy to complete their language assignments, especially in translation courses. Can Google Translate help students learn the target language by promoting language awareness? How might instructors create language assignments using Google Translate to benefit their students? Can linguistic and translation theories be beneficial for translator decisions?